Effect of team quality on offensive playing style and ball possessions development during the 2023 FIFA Women`s World Cup - Iván-Baragaño, I.; Bustamante-Sánchez, Á.; Ardá, A.; Maneiro, R. (Biology of Sport, 2025)
The aim of this study was to investigate the influence of team quality on offensive strategies related to ball possession in the FIFA Women`s World Cup 2023. Additionally, it sought to examine, through bivariate and multivariate analysis, the influence of the initial offensive intention on the development of ball possessions and the different types of possessions executed in this championship. To achieve this, a nomothetic, punctual, and multidimensional observational study was conducted on 2,346 ball possessions. Three types of analyses were performed: i) contingency table analysis to examine the association between team quality and criteria related to ball possessions, ii) factorial ANOVA to explore the interaction between offensive intention and team quality, and iii) two-way cluster analysis to segment the ball possessions. The results revealed statistically significant differences in 12 criteria associated with the start, development, and outcome of ball possessions, both individually and in combination with initial offensive intention. Furthermore, the two-way cluster analysis identified three types of possessions (Direct Attack, Conservative Attack, and Mixed Approach), with statistically significant differences based on team quality. These results may indicate a shift in elite women`s football offensive strategies, where top teams are able to dominate ball possession and manage offensive strategies in terms of duration and offensive intention.